Ceftriaxone in the treatment of chronic donovanosis in central Australia. Issue 2 (April 1994) - Merianos, A; Gilles, M; Chuah, J
Abstract : OBJECTIVES–To determine the effectiveness of intramuscular (IM) ceftriaxone sodium in the treatment of chronic donovanosis, and the acceptability to patients and staff of supervised outpatient treatment in rural clinics. METHODS–We collected demographic and sexual health data from participants using a standard questionnaire, and recorded their donovanosis lesions at baseline using genital diagrams. Treatment consisted of a single daily IM injection of 1 g ceftriaxone diluted in 2 ml of 1% lignocaine. Clinic staff followed patients for between three and 12 months, enabling the detection of late recurrences. SETTING–Rural Aboriginal communities in central Australia. PARTICIPANTS–The study describes eight women and four men with chronic donovanosis in detail, and summarises the outcome in 12 additional cases. All cases presented with advanced lesions which had failed to heal on the standard oral antibiotic regimens used in the region. RESULTS–The mean duration of infection was 3.0 years (SD 1.9 years), and between four and ten courses of antibiotics had been prescribed for six of the 12 patients. Patients received between 7-26g of ceftriaxone sodium. Clinical improvement was dramatic in most lesions, and four patients healed completely without recurrence after a total 7-10g of ceftriaxone. Mild recurrences responded to further ceftriaxone or short courses of oral antibiotics. Treatment was well tolerated, and both patient and staff compliance high. CONCLUSION–Donovanosis is an important cause of chronic genital ulceration in central Australia, and is potentially an important risk factor for HIV transmission in Aboriginal communities. The pharmacokinetics and safety profile of ceftriaxone make it a useful and cost-effective agent in the ambulatory management of donovanosis, especially in remote communities. Supervised multidrug regimens of two or more long-acting agents may provide the best answer in donovanosis, administered through the existing health care infrastructure.